A comparative study of two methods of teaching high school physics - Macaraig, Victoria D. J. (Animo Repository, 1987)
This study investigates the comparative effectiveness of concurrent bilingual approach and the conventional pure English approach in the teaching of High School Physics. The investigative procedure used in the study was the experimental method. It utilized the non-equivalent control group design by Campbell and Stanley (1967). The population consisted of three sections of fourth year high school students of Our Lady Of Caysasay Academy and five sections of fourth year high school students of Rizal College. Each section consisted of 48 students. Two groups, the experimental group and the control group were formed. Each group consisted of one section from Rizal College and one section from Our Lady of Caysasay Academy. The experimental group was taught in the concurrent bilingual approach and the control group was taught in the pure English approach. Both groups were given mental ability tests. Their first periodic rating and mental ability test scores were used as covariates. At the end of the grading period, both groups were given the same achievement test in Physics. All the data used in this study were taken from the physics achievement test, the mental ability test and the first periodic rating in physics. The statistical technique employed in the analysis of data was the analysis of covariance through stepwise regression. All the variables, one dependent (achievement test in physics) and two independent (mental ability and first periodic rating in physics) were included in the regression analysis. In testing the hypothesis, the significance of the F-ratios were evaluated at the .05 probability level. This study showed no statistical significant difference in the performance of students taught in concurrent bilingual approach and in pure English approach. Since mental ability is one of the best predictors of physics achievement, every teacher should know the mental ability of the students for a more effective learning situation to take place. Better learning output may be achieved through proper adjustment of one's methodology to the needs of the learner. Also, since majority of the students prefer the concurrent bilingual approach, more instructional materials or modules for the concurrent bilingual approach should be prepared in answer to the students' needs. An equivalent test in concurrent bilingual approach should likewise be administered to both groups.